Extraction of gaharu essential oil using ultrasonic assisted steam distillation - Ahmad Junaidy, Jaapar (2008)
Aquilaria species from the family of Thymelaeceae are the main source of gaharu, which has been classified as one of the most highly valuable, non-timber products in the world market. Its distinctive fragrance has been valued in many cultures and it is widely used in religious ceremonies, medication, incense, perfume and toiletry products. Currently, the method used for extracting gaharu essential oil is by using hydrodistillation. However, this method is inefficient which it produced low yield of oil and longer time of extraction and thus increasing the production cost. To overcome those problems, this study will be conducted to improve existing method of extraction by using ultrasonic assisted steam distillation. Parameters involve in this study is pretreatment time and gaharu-to-water ratio and both are manipulated to gain high yield of oil with optimum and maximum. The results from this study is the gaharu essential oil yield is increasing with the increment of both pretreatment time and gaharu-to water ratio until it reached a condition where the yield of oil become constant. The best pretreatment time obtained is at 9 hours with oil yield of 0.1276% and the gaharu to water ratio of 1:20.which gave 0.1295% oil yield.